If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -14 = 3x + -14 Reorder the terms: -14 + 11x = 3x + -14 Reorder the terms: -14 + 11x = -14 + 3x Add '14' to each side of the equation. -14 + 14 + 11x = -14 + 14 + 3x Combine like terms: -14 + 14 = 0 0 + 11x = -14 + 14 + 3x 11x = -14 + 14 + 3x Combine like terms: -14 + 14 = 0 11x = 0 + 3x 11x = 3x Solving 11x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 11x + -3x = 3x + -3x Combine like terms: 11x + -3x = 8x 8x = 3x + -3x Combine like terms: 3x + -3x = 0 8x = 0 Divide each side by '8'. x = 0 Simplifying x = 0
| x-1/x^3+2x | | N+17=14+3 | | -6+-12+-10+25= | | (x-3)squared=25 | | 3x^2+9=x^2+27 | | (x-3)/2=25 | | 6x^3-x^2-2x=0 | | 5x/2+12=-8 | | 5g+2g=7g | | 6-7g=-8 | | 6x+10y=50 | | x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 | | x*x^3*x^3= | | (b^2+3b-9)/(b+5) | | 8/c+2-6=4/c+2 | | C(c+2)=12 | | W(w-5)=14 | | 6z-15=3z+12 | | t^2/2+2t=-1/4 | | 1/4(8-8x)=1/2(4x+2) | | 7+4(z-8)=3-3z | | 3x-6=2x+15 | | x-10x+25=0 | | (4v-6)(1+v)=0 |